Biology of breeding poultry - Hocking, P. M. (Paul M.) (Poultry science symposium (Series), 2009)
This book contains chapters that discuss the breeding, reproduction, behaviour, housing, feeding, health and welfare of broiler chickens, turkeys and ducks for meat production.